ChemInform Abstract: Copper‐Mediated Synthesis of Aryldifluoromethylphosphonates: A Sandmeyer Approach. Issue 43 (October 2015) - Bayle, Alexandre; Cocaud, Chloe; Nicolas, Cyril; Martin, Olivier R.; Poisson, Thomas; Pannecoucke, Xavier
Abstract The CuCF2‐PO(O‐Et)2 species, generated in situ under optimized mild conditions, reacts with various aryl diazonium salts to produce the synthetically and pharmaceutically important target compounds bearing various functionalities at the phenyl moiety.